Coastline evolution, submerged landscape, and island occupation: Preliminary insight on Pleistocene-Holocene coastal environments of south-eastern Sicily - Isaac Ogloblin Ramirez; Ehud Galili; Christian A. Tryon; Fabrizio Antonioli; Sara E. Zaia; Peyton Carroll; Elizabeth M. Niespolo; Lauren D. Gilmore; Sebastiano Di Mauro; Fabio Portella; Gianmarco Minniti; Carmelo Monaco; et al. (Quaternary International, 2026)

The dentition of the Early Upper Paleolithic hominins from Ksâr ‘Akil, Lebanon - Shara E. Bailey; Christian A. Tryon (Journal of Human Evolution, 2023)

Biogeographic and Evolutionary Implications of an Extinct Late Pleistocene Impala from the Lake Victoria Basin, Kenya - J. Tyler Faith; Christian A. Tryon; Daniel J. Peppe; Emily J. Beverly; Nick Blegen (Journal of Mammalian Evolution, 2014)

The fossil history of G révy's zebra ( E quus grevyi ) in equatorial East A frica - J. Tyler Faith; Christian A. Tryon; Daniel J. Peppe; David L. Fox (Journal of Biogeography, 2013)
Aim Within the last several decades, G révy's zebra ( E quus grevyi ) has undergone a massive reduction in geographical range and population size, largely as the result of human impacts. To place its recent decline in a deeper prehistoric context, and to understand the factors mediating its range and abundance over geological time frames, this study examines the fossil history of G révy's zebra in equatorial E ast A frica. Location Equatorial E ast A frica. Methods Presence/absence data for ungulates recovered from fossil sites spanning the last c . 400,000 years in K enya and E thiopia were compiled from the literature and from previously unreported palaeontological sites. Associations between G révy's zebra and other taxa were examined using principal coordinates analysis and non‐random species pairs were identified using a Bayesian approach. Changes in rainfall were reconstructed using the average hypsodonty index of ungulate species from fossil assemblages. Results G révy's zebra was common during dry phases of the P leistocene and was found to the south and west of its historical range, coinciding with an expansion of arid grasslands. At the onset of the H olocene, G révy's zebra was extirpated from southern K enya and almost completely disappeared from the fossil record. G révy's zebra was associated with several specialized grazers that became extinct by the end of the Pleistocene. These extinctions and the decline of G révy's zebra from the P leistocene to the H olocene are explained by increased precipitation and the consequent loss of arid grasslands at the P leistocene– H olocene transition. G révy's zebra is never associated with domestic livestock, unlike the widespread plains zebra. Main conclusions Grévy's zebra thrived in equatorial E ast A frica during periods of the P leistocene when environmental conditions favoured an expansion of arid grasslands. Environmental change across the P leistocene– H olocene transition contributed to decreases in the range size and abundance of G révy's zebra, setting the stage for the anthropogenic decline observed in recent decades. The spread of pastoralists in the middle H olocene may have additionally contributed to its prehistoric decline. Contemporary climate change warrants further consideration in planning for the long‐term survival of G révy's zebra.

Reinvestigating Early Human Behavior at Olduvai Gorge - Christian A. Tryon (Journal of Mammalian Evolution, 2008)